DETERMINATION OF RESIDUAL OXYTETRACYCLINE IN FISHES BY HIGH PERFORMANCE LIQUID CHROMATOGRAPHY [Determinasi residu oxytetracycline pada ikan dengan menggunakan HPLC] - Djamartumpal F. Lumban Batu (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2010)
A high performance liquid chromatography method (HPLC) was developed for the determination of oxytetracycline (OTC) residues in fishes. OTC was extracted from fish tissues with 5% trichloroacetic acid containing 5% disodium ethylenediaminetetraacetate (Na2EDTA). The extract was centrifuged and concentrated. The concentrated solution was washed with n-hexane and passed through a Sep-pak C18 cartridge. The cartridge was washed with distilled water, before use. Elute OTC with methanol and evaporate to dryness. The residue was dissolved in acetonitrile-distilled water (3:7), and determined by HPLC (with absorbance measurement at 360 nm) on a TOSOH TSK-GEL ODS 80 Tm Column (250 mm x 4,6 mm) with methanol-acetonitrile-0.2 M oxalic acid (1 : 1 : 4.4; pH 2,0) as a mobil phase. The average recoveries of OTC from blood, liver, muscle and kidney of rainbow trout, Oncorhynchus mykiss were 90, 72, 84, and 73%, respectively. The detection limits for muscle was 0.05 ppm, and those for liver and kidney were 0.1 ppm.